Generation of Neural Progenitor Cells from Pig Embryonic Germ Cells - Kwang-Hwan Choi; Dong-Kyung Lee; Jong-Nam Oh; Seung-Hun Kim; Mingyun Lee; Jinsol Jeong; Gyung Cheol Choe; Chang-Kyu Lee (The Korean Society of Animal Reproduction and Biotechnology, 2020)
As a preclinical study, many researchers have been attempted to convert the porcine PSCs into several differentiated cells with transplantation of the differentiated cells into the pigs. Here, we attempted to derive neuronal progenitor cells from pig embryonic germ cells (EGCs). As a result, neuronal progenitor cells could be derived directly from pig embryonic germ cells through the serum-free floating culture of EB-like aggregates (SFEB) method. Treating retinoic acid was more efficient for inducing neuronal lineages from EGCs rather than inhibiting SMAD signaling. The differentiated cells expressed neuronal markers such as PAX6, NESTIN, and SOX1 as determined by qRT-PCR and immunostaining. These data indicated that pig EGCs could provide valid models for human therapy. Finally, it is suggested that developing transgenic pig for disease models as well as differentiation methods will provide basic preclinical data for human regenerative medicine and lead to the success of stem cell therapy.